The Role of Maternal Age and Ethnicity on Pregnancy Complications and Mode of Birth, and an Examination of Maternity Trends Amongst Primiparous Women in Western Australia - Catalano, Nicole (Curtin University, 2024)
Welcoming a baby is a joyous occasion for many families. My longitudinal analysis of a decade of perinatal data on West Australian women has highlighted notable changes in the health of primiparous women’s pregnancies and birth experiences. Providing women and their families with ongoing education from preconception and throughout pregnancy may improve outcomes at a personal and population level.